Handbook of multilevel metallization for integrated circuits materials, technology, and applications - Wilson, Syd R.; Tracy, Clarence J.; Freeman, John L. (Materials science and process technology series. Electronic materials and process technology., 1993)
It is widely recognized that the successful design, development, and integration of multilevel metallization (MLM) systems is and will continue to be key to current and future VLSI technologies. All major semiconductor companies have significant ongoing research teams focused in this area. These teams must view multilevel metallization as a system rather than a collection of isolated process modules.